Indicators of professional competencies in research of Guidance and Counseling Teachers - Supriyanto, Agus; Hartini, Sri; Syamsudin, Syamsudin; Sutoyo, Anwar (Universitas PGRI Madiun, 2019)
Competence counselor in guidance and counseling research needs to be developed through understanding, planning, implementing, and utilizing research results. The purpose of the study was to design indicators of counselor competency in guidance and counseling research. The type of research is qualitative with literature study design. Primary documents through books, journals, scientific articles, and relevant policies for indicator development from the competence of school counselors in research. Qualitative data analysis with the form of social policy analysis through the process of data reduction, data presentation, and data inference. The findings reveal that four indicators were understanding various types and methods of research, ability to design research, conduct research, and use research results by accessing journals of education and guidance and counseling. Each indicator has a sub indicators that need to be tested. Hope in the future is reveal the level or evaluation of the competence of school counselors in guidance and counseling research.